30+12x = 6(5+2x)
(2x + 3)(2x + 3)
(x-3)(x-9) = 0
2(x - 2)(x - 4)
The answer to -12x minus 17 equals negative 89 is x equals 6.
30+12x = 6(5+2x)
9x2
(2x + 3)(2x + 3)
6x3 - 27x2 + 3x + 36 = 3 (x - 4) (x + 1) (2x - 3)
3x(2x - 5)(x + 7)
(x-3)(x-9) = 0
2(x - 2)(x - 4)
The answer to -12x minus 17 equals negative 89 is x equals 6.
(12x - 6)(12x + 6)
-9x 2 -12x+5 =
x2+12x-13=0 The factor of x2+12x-13 is: (x+13)(x-1) So: x+13 = 0 or x-1 = 0 The answer is: x=-13 or x=1
=>2x - 12x + 36 = 0 =>10x = 36=>x = 3.6Another contributor's answer:This is a quadratic equation question:x2-12x+36 = 0When factorised:(x-6)(x-6) = 0